Epidemiology of gout and chondrocalcinosis - M. Govoni; A. Bortoluzzi; G. Ciancio (PAGEPress Publications, 2012)
Gout is the most common cause of inflammatory arthritis affecting at least 1% of the population in industrialized countries. It is closely associated with hyperuricemia and is characterized by formation and reversible deposition of monosodium urate crystals in joints and extra-articular tissues. Several studies suggest that the prevalence and incidence of gout are rising. Numerous risk factors may in part explain this increasing trend including dietary and lifestyle changes, genetic factors, diuretic use and comorbid conditions such as hypertension, diabetes, cardiovascular disease, chronic renal disease and the metabolic syndrome. Chondrocalcinosis is characterized by the deposition of calcium pyrophosphate crystals in articular tissues, most commonly fibrocartilage and hyaline cartilage. Sporadic chondrocalcinosis is a common condition in the elderly and frequently associates with osteoarthritis. Hereditary haemochromatosis, hyperparathyroidism and hypomagnesaemia are metabolic disorders that predispose to secondary chondrocalcinosis.The prevalence of chondrocalcinosis is still rather uncertain and varies depending on the diagnostic criterion used in different studies.